Thermal sweating responses in swimmers - Taimura, A.; Sugawara, M.; Yamauchi, M.; Lee, J. B.; Matsumoto, T.; Kosaka, M. (Medicine & Science in Sports & Exercise, 1998)
The thermal sweating responses of swimmers (college males N = 13) and other land-trained athletes (college males N = 14) were compared. Heat loads were applied to the legs by immersion in a hot water bath (43 degrees Celsius) for 30 minutes in a climate chamber (26 degrees Celsius). Tympanic, sublingual, chest, thigh, abdomen, forearm, and back temperatures and sweat rates were measured. For all regions, the local sweat volumes in the swimming group were smaller than for the land group. Swimmers' mean body and skin temperatures were lower than those of the land group. Implication: Swimmers and land-trained athletes differ significantly in heat tolerance and sweating responses.